Insect and disease resistance from tropical maize for use in temperate zone hybrids - Kim, S.K.; Brewbaker, J.L.; Hallauer, A. (1988)
Biotic constraints (insects, diseases, parasitic weeds) and abiotic stresses (drought) are widespread and pose a constant threat to maize production worldwide. Tropical environments provide the greatest opportunity for evolution of insects and diseases because of the favourable year- round climatic conditions. Year-round breeding programs permit selection of stable general resistance against specific or combined challenges. The IITA Maize Program initiated a line-development project in 1979. The major objectives of this project were to develop vigorous, tropically adapted inbreds that confer general resistance or tolerance against specific African as well as common tropical production constraints. Important constraints in Africa are stem borer (Sesamia calamistis, Eldana saccharina and Busseola fusca), storage insects (Si-tophi/us spp.), foliar diseases (Maize Streak Virus, Puccinia palysora, Hel•mintho.parium maydu, Exserohilum turcicum, Curvularia palle.cens.downy mildew), stalk and ear rots (Fusarium moniliform, Botryodiplodiat Mobromae, Macrophomina phauolii, Striga hermonthica, and drought. Some of these problems occur in the U.S. Com Belt and in other parts of the world. The Maize Inbred Resistance (MIR) project of the University of Hawaii tested 120 tropically adapted inbred collections at 27 locations worldwide, including tropical. Sub-tropical and temperate regions. Sources for high levels of general resistance were found for most insects and diseases. The selected inbreds could be valuable sources of resistance for developing inbreds and hybrids adapted to the Com Belt. This paper presents current results regarding general resistance to the major production constraints of maize worldwide and introduces a pioneering approach for testing combining ability of tropical inbreds for temperate as well as tropical regions.